Pengaruh Job Crafting dan Tuntutan Kerja Terhadap Kepuasan Kerja Karyawan - Hasibuan, Muhammad Rizky; Adlina, Hafiza; Siregar, Onan Marakali (Peneliti.net, 2025)
Developments in the business world make companies must have quality human resources (HR) in the face of change and competition. The importance of employee job satisfaction can affect the quality of performance it produces for the company in the face of change and competition which are work demands for employees. Facing work demands, employees can practice job crafting by taking the initiative to adapt their tasks to their expertise in facing work demands and obtaining job satisfaction for their work achievements. This study aims to determine the effect of job crafting and job demands on employee job satisfaction at PT Infiniti International Logistic Medan. This research uses quantitative methods with 48 employees as research samples. Primary data collection is done through questionnaires distributed to respondents directly, while secondary data is obtained from literature studies. The results of the study found that job crafting and work demands have a significant effect on job satisfaction of employees of PT Infiniti International Logistic Medan by 29.3%. This means that job crafting and employee work demands have motivated employees to develop their abilities to obtain job satisfaction.